Inteligencia artificial, discurso digital y lenguaje: La lingüística en la era de las nuevas tecnologías - Lovón, Marco (2024)
In recent years, technology has expanded and generated social transformations. The rapid spread of AI, as well as the development of communications or discourse in the digital space, has attracted the attention of linguists, who are called upon to respond to technological innovation and its repercussions. The aim of this paper is to highlight the scientific-academic work of linguistics in the era of new technologies and digital spaces. To this end, the following events are highlighted: 1) the International Congress “Artificial Intelligence, Digital Discourse and Language”; 2) the thematic dossier about this topic published in this issue of the journal Lengua y Sociedad; 3) the relationship between artificial intelligence and linguistics, and 4) the relationship between digital discourses and linguistics. With this research, the publication and thematic works on artificial intelligence and digital discourse in interaction with language are highlighted.